2004
DOI: 10.1158/1078-0432.ccr-04-0145
|View full text |Cite
|
Sign up to set email alerts
|

Cytochrome P450 and Glutathione Transferase Expression in Squamous Cell Cancer

Abstract: Purpose: The cytochrome P-450 (CYP) and glutathione S-transferase (GST) enzyme systems modulate the carcinogenic effects of tobacco. Therefore, the expression of these enzymes may be in part responsible for the observed interindividual and inter-racial differences in the risk of development of squamous cell carcinoma of the head and neck (SCCHN). The first aim of this study was to evaluate the feasibility of measuring the expression of the CYP and GST in target tissue from the head and neck. The second aim was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
10
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 30 publications
3
10
0
Order By: Relevance
“…The relationship between GSTP1 expression and carcinogenesis has been differently reported in OSCC . The inconsistent results might be caused by large individual variability in the expression of GSTP1 enzymes in different patients . In our study, we confirmed the decreased GSTP1 expression in OSCC, not only in OSCC lines, but also in patients with OSCC and a correlation between the GSTP1 expression and differentiation of the tumor was also found.…”
Section: Discussionsupporting
confidence: 81%
“…The relationship between GSTP1 expression and carcinogenesis has been differently reported in OSCC . The inconsistent results might be caused by large individual variability in the expression of GSTP1 enzymes in different patients . In our study, we confirmed the decreased GSTP1 expression in OSCC, not only in OSCC lines, but also in patients with OSCC and a correlation between the GSTP1 expression and differentiation of the tumor was also found.…”
Section: Discussionsupporting
confidence: 81%
“…It achieves so by undergoing metabolic activation by cytochrome P450 2E1 and generates electrophilic substances that form DNA adducts . Therefore, in chemically induced carcinogenesis, carcinogen activating enzyme expression is a critical component as it holds a very high proliferative potential of pushing usual cells to a cancerous phenotype . In the present study, the raised the activities of the cytochrome P450 family enzymes in colonic mucosa DMH treated rats was observed.…”
Section: Discussionsupporting
confidence: 50%
“…A higher frequency of G to T transversion has been documented in animals exposed to PAH carcinogens (37). The enhanced activities of phase I and II enzymes as well as increased expression of 8-OH-dG seen in HBP tumours in the present study corroborate overexpression of these enzymes and oxidative DNA damage reported in cell lines and malignant tumours (26,38,39).…”
Section: Biochemical Findingssupporting
confidence: 88%